Bioecology of Sargassum sp. and its Extract Bioactivity as Anti-MDR Bacteria - Rini Pramesti; Wilis Ari Setyati; Muhammad Zainuddin; Maya Puspita (Marine Science Department Diponegoro University, 2017)
This study was done to investigate the bioecology and extract bioactivity of Sargassum sp from Jepara district. Seaweed was collected from Teluk Awur, Panjang Island, Bandengan, Ujung Piring and Bondo. There were seven species of Sargassum identified i.e. S. duplicatum, S. polycystum, S. echinocarpum, S. cinerium, S. crassifolium, S. plagyophillum and S. binderi. Community structure indices were calculated based on data collected by survey. Antibacterial activity of Sargassum extract was done on MDR bacteria. The results showed that diversity index at Panjang Island, Bandengan, and Ujung Piring were categorized as medium, while Teluk Awur and Bondo were categorized as low. Evenness index was high at Teluk Awur, Panjang Island, Bandengan and Ujung Piring and Bondo was low. There was no dominant species found in most of the locations. The principal component analysis exhibited the main variable that affected the Sargassum at Teluk Awur was phosphate, Panjang Island was depth, Ujung Piring was salinity and Bondo was temperature, dissolved oxygen and pH, respectively. There was character similarity between Panjang Island and Bandengan (99.73%), meanwhile, at Teluk Awur, Ujung Piring, and Bondo, the similarity was 99.62%, 99.60%, and 99.52%, respectively. Antibacterial activity of Sargassum sp. demonstrated a positive activity against the MDR bacteria, Staphylococcus aureus (6.28±0.04 mm), Escherichia coli (6.96±0.19 mm), and S. epidermidis (12.65±0.23 mm). Clustering analysis of extracts with bactericidal characteristic found three classes with similarity of class 1, 2 and 3 at 72.33%, 76.80% and 58.50%, respectively. Sargassum sp. was categorized in class 1 had the best antibacterial activity and the highest abundance value. Keywords: ecology, community, Sargassum sp., extracts, antibacterial